Чернігівщина в Лівонській війні - Ігнатенко, І. (Сiверянський лiтопис, 2019)
Стаття присвячена вивченню перебігу подій Лівонської війни на території Чернігово-Сіверщини. Досі історики пропонували різні дати боїв, що відбувалися в ході неї під
стінами Чернігівської фортеці. У результаті аналізу різнорідних джерел автор дійшов
висновку, що Чернігів піддавався нападу лише двічі, у 1564 та 1579 р. Детальні описи
боїв у ході Лівонської війни на Чернігово-Сіверщині містяться в історичній праці польського історика XVI ст. Б. Папроцького. Однак він неправильно вказав дати військових
сутичок. Б. Папроцький об’єднав у своїй праці різночасові епізоди бойових зіткнень в
єдиний блок, щоб підкреслити військові подвиги Філона Кміти. Порівнявши ці відомості
з іншими документами, автор уточнив дати військових акцій росіян і литовців, котрі
відбувалися в ході Лівонської війни на території Чернігово-Сіверської землі. The article is devoted to studying the course of events of the Livonian war on the territory
of the Chernihiv-Sivershchina. Until now, historians have offered different dates for
the battles that took place in the course of this war under the walls of the Chernihiv fortress.
It was believed that such battles took place in 1552, 1562, 1564, 1565 and 1579. The author
compared data from various sources: Lithuanian chronicles and official documents, Russian
«Books of Ranks», works by Polish historians of the 16th century. These sources have varying
degrees of reliability. As a result of the analysis of the information received, the author came
to the conclusion that Chernihiv was attacked only twice, in 1564 and 1579. In addition, there
were other hostilities on the territory of Chernihiv- Sivershchyna land. In particular, in 1562,
between the cities of Chernihiv and Oster, two battles of Lithuanians against the Russians
took place. In these battles, the Lithuanians, led by the governor of the castle of Oster, Philon
Kmyta, won. In 1563, the Lithuanian army under the command of Prince Mikhail Vishnevetsky
attacked the Russian part of Chernihiv-Sivershchyna. On the way back, when crossing
the Desna River, the detachment of M. Vishnevetsky was defeated by the Russians. Detailed
descriptions of the battles that took place in the Chernihiv-Sivershchyna region during the
Livonian War are contained in the historical work of the 16th century Polish historian Bartosz
Poprotsky. Comparing this story with other documents, the author suggested that B. Paprotsky
incorrectly indicated the dates of military clashes. Polish historian combines episodes of clashes
occurring at different times in a single unit. The purpose of such an editing of the text was
an attempt to emphasize the feats of Philon Kmita. Comparison of the historical narrative
of B. Paprotsky with the act documents dated 1579 showed a number of coincidences. Thus,
the author specified the dates of the military actions of the Russians and Lithuanians, which
took place during the Livonian War on the territory of the Chernihiv-Sivershchyna land.